Pain and Neurocognitive Outcomes After Non-Cardiac Surgery in Older Adults - Khaled, Maram (My University, 2023)
Neurocognitive events after surgery, can occur as an acute event, such as postoperative delirium (POD) or in the form of decline in cognitive performance in the early or delayed postoperative period such as postoperative cognitive dysfunction (POCD). Neurocognitive events are patient- important outcomes which are associated with an increased risk of adverse outcomes. Surgery has been suggested to be a trigger for POD and to be associated with cognitive decline after surgery. Postoperative pain is common after surgery, and it is biologically plausible for pain to play a role in the development of neurocognitive outcomes. This thesis comprises six chapters focusing on pain and neurocognitive outcomes after non-cardiac surgery in older patients. Chapter 1 is an introduction and rationale for the included studies. Chapter 2 is a protocol for a series of systematic reviews to summarize the evidence regarding the association between postoperative pain (acute and chronic) and opioid-sparing pain management strategies for acute and chronic postoperative pain, and the incidence of POD and POCD. Chapter 3 reports the results of a systematic review and dose-response meta-analysis of observational studies evaluating the association of postoperative pain and POD and POCD. Chapter 4 describes a methodological approach to evaluate the robustness of meta-analyses with POD as an outcome to the variation in the methods (timing and frequency) of POD assessment. Chapter 5 presents the results of the Co-TELESURGE study, a longitudinal prospective cohort study of perioperative cognitive trajectories in older adults who were waiting for elective non-cardiac surgery during the COVID-19 pandemic. Chapter 6 discusses the key findings, limitations, implications for research, future recommendations and final conclusions of the research presented in this doctoral thesis.
Keywords: Pain; Cognition; Delirium; Surgery; Perioperative care; Meta-analysis